31-Year-Old Female Shows Marked Improvement in Depression, Agitation, and Panic Attacks after Genetic Testing Was Used to Inform Treatment. (18th March 2014) - Lawrence, Scott
Abstract : This case describes a 31-year-old female Caucasian patient with complaints of ongoing depression, agitation, and severe panic attacks. The patient was untreated until a recent unsuccessful trial of citalopram followed by venlafaxine which produced a partial response. Genetic testing was performed to assist in treatment decisions and revealed the patient to be heterozygous for polymorphisms in 5HT2C, ANK3, and MTHFR and homozygous for a polymorphism in SLC6A4 and the low activity (Met/Met) COMT allele. In response to genetic results and clinical presentation, venlafaxine was maintained and lamotrigine was added leading to remission of agitation and depression.